PENGEMBANGAN MODUL AJAR DENGAN PENDEKATAN SETS (SCIENCE, ENVIRONMENT, TECHNOLOGY AND SOCIETY) BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR SISWA - SELY ANTIKA (UNIVERSITAS HAMZANWADI, 2026)
This study aims to develop a teaching module based on the SETS (Science, Environment, Technology, and Society) approach to improve student learning outcomes. The research and development followed the Borg and Gall model, comprising seven stages: 1. Preliminary research and information gathering, 2. Planning, 3. Initial product development, 4. Preliminary testing, 5. Product revision, 6. Field testing, and 7. Final product revision. The subjects of the study were 99 students from SMAN 1 Sakra Timur. Data collection was conducted using questionnaires and tests, and the data were analyzed using quantitative descriptive analysis techniques. The analysis revealed validity coefficients of 96.06% and 90.04% from subject matter experts and 92.08% from design experts, all falling within the